2000
DOI: 10.1111/j.1601-0825.2000.tb00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Mechanisms: Reactive oxygen species: a potential role in the pathogenesis of periodontal diseases

Abstract: The pathological events leading to the destruction of the periodontium during inflammatory periodontal diseases are likely to represent complex interactions involving an imbalance in enzymic and non‐enzymic degradative mechanisms. This paper aims to review the increasing body of evidence implicating reactive oxygen species (ROS), derived from many metabolic sources, in the pathogenesis of periodontal tissue destruction. ROS are generated predominantly by polymorphonuclear leukocytes (PMN) during an inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
321
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(335 citation statements)
references
References 170 publications
6
321
0
8
Order By: Relevance
“…They can damage (via oxidation) proteins, lipids, carbohydrates, and nucleic acids and ultimately contribute to a number of pathogenetic processes in a variety of inflammatory disorders. Reactive oxygen species (ROS) include oxygen-derived free radicals, such as superoxide, hydroxyl, nitric oxide, hydrogen peroxide, and hypochlorous acid (Waddington et al 2000, Canakci et al 2005. Oxidative stress is defined as the condition arising from a serious abundance of the levels of free radicals in a cell in comparison to its antioxidant defences (Singh & Jialal 2006).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…They can damage (via oxidation) proteins, lipids, carbohydrates, and nucleic acids and ultimately contribute to a number of pathogenetic processes in a variety of inflammatory disorders. Reactive oxygen species (ROS) include oxygen-derived free radicals, such as superoxide, hydroxyl, nitric oxide, hydrogen peroxide, and hypochlorous acid (Waddington et al 2000, Canakci et al 2005. Oxidative stress is defined as the condition arising from a serious abundance of the levels of free radicals in a cell in comparison to its antioxidant defences (Singh & Jialal 2006).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The mechanisms via which antioxidants protect biological systems from oxidative damage include the direct scavenging of ROS and the sequestration of free catalytic metal ions, which promote ROS formation (10) . There is some evidence of a negative association between antioxidant status and periodontal disease.…”
mentioning
confidence: 99%
“…36 Remarkable study suggest that oxidative stress plays an essential role in the periodontal and alveolar bone destruction. 37 Previous study also reported the connection between clinical attachment level with the escalation of reactive oxygen metabolites (ROM). 38 Moreover, mitochondria as the major producer of ROS in cells causes a chronic over production which leads to increased oxidation of LDL in atherosclerosis development.…”
Section: Discussionmentioning
confidence: 99%